Studies on HIF hydroxylases - Webb, J (2008)
Hypoxia-inducible factor (HIF) is the master regulator of genes involved in adaptation to hypoxia. The stability and transcriptional activity of HIF are regulated by post-translational hydroxylations: prolyl hydroxylation by the prolyl hydroxylase domain-containing enzymes PHD1 – 3 earmarks HIF for proteasomal degradation, whilst asparaginyl hydroxylation by factor inhibiting HIF (FIH) blocks the interaction of HIF with the transcriptional coactivators p300/CBP. The PHDs and FIH hydroxylate HIF directly from molecular oxygen and are therefore oxygen sensors. Recent literature shows that FIH also hydroxylates a number of proteins containing an ankyrin-repeat domain (ARD). Together with reports suggesting that the PHDs are involved in HIF-independent pathways, this suggests that the HIF hydroxylases may have a wide range of non-HIF targets. This thesis describes my investigations into novel substrates of the HIF hydroxylases. This work has characterized the FIH-dependent hydroxylation of the ARD-containing protein Notch1, and defined a consensus sequence for hydroxylation that corresponds to the ankyrin-repeat consensus. Using this consensus potential sites of hydroxylation in a novel ARD FIH substrate, myosin phosphatase targeting subunit 1 (MYPT1), were identified then subsequently confirmed and characterized. Notch1 competes with HIF for FIH hydroxylation. My experiments show that this occurs because Notch1 is a more efficient substrate than HIF, whilst studies on MYPT1 and other proteins indicate that competitive inhibition of FIH may be a general property of ARDs. There are more than 300 ARD proteins in the human genome, and this thesis demonstrates that FIH may hydroxylate a significant percentage of these. In addition to the analysis of ARD hydroxylation a proteomic investigation into novel PHD3 substrates has identified two candidate proteins, suggesting that the PHDs may also have multiple targets. These results have important implications for oxygen sensing, and indicate that post-translational hydroxylation is likely to be a widespread modification in cell biology.